Cytokine expression and lymphocyte proliferative capacity in diseased harbor porpoises (Phocoena phocoena) – Biomarkers for health assessment in wildlife cetaceans. (April 2019) - Lehnert, Kristina; Siebert, Ursula; Reißmann, Kristina; Bruhn, Regina; McLachlan, Michael S.; Müller, Gundi; van Elk, Cornelis E.; Ciurkiewicz, Malgorzata; Baumgärtner, Wolfgang; Beineke, Andreas
Abstract: Harbor porpoises ( Phocoena phocoena ) in the North and Baltic Seas are exposed to anthropogenic influences including acoustic stress and environmental contaminants. In order to evaluate immune responses in healthy and diseased harbor porpoise cells, cytokine expression analyses and lymphocyte proliferation assays, together with toxicological analyses were performed in stranded and bycaught animals as well as in animals kept in permanent human care. Severely diseased harbor porpoises showed a reduced proliferative capacity of peripheral blood lymphocytes together with diminished transcription of transforming growth factor-β and tumor necrosis factor-α compared to healthy controls. Toxicological analyses revealed accumulation of polychlorinated biphenyls (PCBs), dichlorodiphenyldichloroethylene (DDE), and dichlorodiphenyltrichloroethane (DDT) in harbor porpoise blood samples. Correlation analyses between blood organochlorine levels and immune parameters revealed no direct effects of xenobiotics upon lymphocyte proliferation or cytokine transcription, respectively. Results reveal an impaired function of peripheral blood leukocytes in severely diseased harbor porpoises, indicating immune exhaustion and increased disease susceptibility. Graphical abstract: Image 1 Highlights: Biomarkers for health assessment in wildlife cetaceans were investigated. Associate real world PCB levels with immune dysfunction in harbor porpoises. Blood PCB levels associated with health and immune markers. Reduced proliferative capacity of lymphocytes in diseased harbor porpoises. Diminished cytokine transcription of TGF-β and TNF-α in diseased harbor porpoises. Abstract : Lymphocyte proliferation assays and cytokine expression analyses represent adjuvant tools to determine immune function in wild harbor porpoises.